Biomechanical assessment of different kinds of fixing of unstable fractures in the acetabular region of the femur in experiment - Yuriychuk, Lyubomyr; Poluliakh, Mykhaylo; Klepach, Mykola; Shidlovsky, Mykola; Popovych, Yuriy; Pavlischen, Yuriy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2012)
Unstable (A3) fractures in the acetabular region of the femur in the acetabular region of the femur were experimentally modelled on 18 preparations from cadaver bones of elderly people. The preparations were divided into three groups, by 6 in each. Fragments were fixed with a cemented endoprosthesis stem in group 1, with a DHS plate in group 2, and 130 degree angle plates in group 3. Biomechanical studies of the fragment fixation resistance to axial loads, fractures and maximum dynamic axial loads were conducted. Results of the above studies demonstrated a high rigidness of fracture fixation with angle plates and a low resistance of fragments to maximum compression loads. In osteosynthesis with DHS plates, preparations bore weight up to 140 kg, but turned out to be half resistant to cyclic and fracture loads versus their fixation with angle plates and one-eighth as strong (up to 12 %) as when fixed with endoprostheses. In cases of fixing with wire, screws and endoprosthesis stems with cement, resistance to loads was close to that of an intact bone.